THE IMPACT OF ESG DISCLOSURE, LEVERAGE, AND FIRM SIZE ON THE COMPANIES’ FINANCIAL PERFORMANCE - Michelle Gracella; Yanti Yanti (International Journal of Application on Economics and Business, 2026)
Sustainability and corporate governance issues are increasingly crucial for investors, while strategic decisions regarding capital structure and scale of operations determine a company's resilience amid fluctuating global commodity prices. The 2020–2022 period reflects a recovery phase that demanded rapid adaptation and efficient resource allocation from energy companies. Therefore, an in-depth study is needed to determine how these internal factors influence the ability of energy companies to generate profits. This study aimed to examine the impact of ESG disclosure, leverage, and firm size on company financial performance, as measured by the ROA proxy. This study used data from 91 energy sector companies listed on the Indonesia Stock Exchange for the period 2022 to 2024. This study employed a quantitative method and a purposive sampling technique. This analysis used panel data regression model with a Random Effects Model (REM) approach, processed using the eViews program. The results of this study indicate that ESG disclosure had a negative but insignificant effect on financial performance. Meanwhile, leverage-as another independent variable-has been shown to have a negative and significant impact on company financial performance. Furthermore, firm size has been shown to have a positive and significant impact on company financial performance. To improve future research, it is recommended that researchers increase the sample size by extending the research period and/or expanding the scope of the company sector, as well as incorporating under-researched variables such as Net Interest Margin or Non Performing Loans, which have the potential to impact the company's financial performance.